2021
DOI: 10.1108/ijchm-08-2020-0877
|View full text |Cite
|
Sign up to set email alerts
|

Employer event communication and hospitality workers’ resilience during the COVID-19 crisis: the role of core beliefs examination and family support

Luu Trong Tuan

Abstract: Purpose Hospitality is one of the industries severely impacted by the COVID-19 pandemic. It is vital to comprehend how to help the workforce in this service sector grow resilient through such a crisis. This paper aims to unpack the role of employer event communication in promoting hotel workers’ resilience. Design/methodology/approach The data were garnered from 462 hotel workers who were on unpaid leave or layoff during the hotel shutdown. Findings The results unfolded the positive link between employer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 121 publications
4
20
0
Order By: Relevance
“…Resilience increases employees' ability to cope effectively with challenges, such as mental health disorders, traumatic job experiences, or adverse workplace conditions. The results of the present exploratory study support Tuan (2021), who argues that employees' positive emotions and experiences can promote the psychological capabilities required for resilience while their beliefs may enable employees to make more positive meanings out of their experiences.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Resilience increases employees' ability to cope effectively with challenges, such as mental health disorders, traumatic job experiences, or adverse workplace conditions. The results of the present exploratory study support Tuan (2021), who argues that employees' positive emotions and experiences can promote the psychological capabilities required for resilience while their beliefs may enable employees to make more positive meanings out of their experiences.…”
Section: Discussionsupporting
confidence: 84%
“…This reduces their stress in the workplace and social life (Ong et al, 2006), and overcomes the problem before the trauma (Thompson et al, 2011). The positive effect of hotel employees' psychological resilience on their mental health perceptions confirms previous research findings (Chen & Bonanno, 2020;Hall et al, 2017;Tuan, 2021;Yu, 2020). In addition, in terms of the Broaden-and-Build Theory, hotel employees with greater psychological resilience can expand their thoughtaction repertoire based on previous difficulties and experiences.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Given that theories in the hospitality and event literature informing the relationships between the perceived fit of recovery strategies and organization commitments are scarce, we relied heavily on theoretical notions and empirical evidence from the strategic management and organizational behavior literature to develop the conceptual model for the present study. Although hospitality and tourism studies have covered crisis and risk management fields to address the recent COVID-19 crisis in various sectors, including hotels (Giousmpasoglou et al , 2021; Tuan, 2021), restaurants (Kim et al , 2021), cruises (Castaldo et al , 2021) and events (Wong et al , 2021), it is still far from having enough evidence to properly guide the industry navigate into new normality, especially those sectors outside of accommodation (Ritchie and Jiang, 2021). Hospitality research on strategic management and organizational behavior in the context of hotel and restaurant employees has focused on perceived fits between a corporate strategy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies found that internal crisis communication directly relates to employee and organizational resilience, employees' sense of psychological safety at the workplace, and commitment to and support of the employer ( Guzzo et al, 2021 , Tuan, 2021 ). In managing hospitality and tourism organizations, recent studies ( Guzzo et al, 2021 , Tuan, 2021 ) found the positive impacts of employers' communication behaviors on bolstering positive employer-employee dynamics during COVID-19. These attempts, however, have not revealed the direct impacts of these communicative behaviors on employee resilience and turnover intentions.…”
Section: Introductionmentioning
confidence: 98%